2012
DOI: 10.1016/j.scitotenv.2011.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Real-time estimation of small-area populations with human biomarkers in sewage

Abstract: A new approach is conceptualized for measuring small-area human populations by using biomarkers in sewage. The basis for the concept (SCIM: Sewage Chemical-Information Mining) is supported by a comprehensive examination and synthesis of data published across several disciplines, including medicine, microbiology, clinical chemistry, and environmental science. Accurate measures of human populations are fundamental to numerous disciplines, including economics, marketing, politics, sociology, public health and saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
94
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(97 citation statements)
references
References 145 publications
2
94
0
1
Order By: Relevance
“…It is the most abundant sterol in human faeces and, consequently, is frequently used as an urban sewage tracer (DAUGHTON, 2012). GONZÁLEZ-OREJA and SAIZ-SALINAS (1998) have suggested that coprostanol concentrations greater than 0.50 µg g -1 may be used to indicate sewage contamination.…”
Section: Discussionmentioning
confidence: 99%
“…It is the most abundant sterol in human faeces and, consequently, is frequently used as an urban sewage tracer (DAUGHTON, 2012). GONZÁLEZ-OREJA and SAIZ-SALINAS (1998) have suggested that coprostanol concentrations greater than 0.50 µg g -1 may be used to indicate sewage contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Different approaches were used to estimate the population served by each STP due to the specific characteristics of the individual sewer systems investigated (i.e. census data, number of house connections or drinking water subscribers, or using a measured biological parameter in sewage; BOD, COD, N, and P; Andreottola et al, 1994;Zessner and Lindtner, 2005;Daughton, 2012). The variability among the different population estimates obtained was found to be between 7 and 40% (%RSD) and is strictly dependent on the sewage composition (i.e.…”
Section: Normalization and Estimation Of Usementioning
confidence: 99%
“…The de facto population connected to an STP may not coincide with the determined de jure population 11,13 . It is because the former is population equivalent and accounts for tourist and the difference between daytime and nighttime populations, while the later is based on the latest census.…”
Section: Introductionmentioning
confidence: 97%